Extinction, weak extinction and persistence in a discrete, competitive Lotka-Volterra model - Chan, David M.; Franke, John E. (Zielona Góra: Uniwersytet Zielonogórski)
In a discrete Lotka-Volerra model, the set of points where a population remains unchanged over one generation is a hyperplane. Examining the relative position of these hyperplanes, we give sufficient conditions for a group of species to drive another species to extinction. Further using these hyperplanes, we find necessary and sufficient conditions where every [omega]-limit point of the model has at least one species missing.
Keywords: extinction; persistence; weak extinction; Lotka-Volterra model; [omega]-limit set